The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.12688/f1000research.24123.2
|View full text |Cite
|
Sign up to set email alerts
|

The use of essential oils as a growth promoter for small ruminants: a systematic review and meta-analysis

Abstract: Background: Due to their antimicrobial properties and safety, essential oils are currently proposed as a sustainable option for antibiotic alternatives in the livestock sector. This current systematic review and meta-analysis investigated the effects of dietary essential oil supplements on dry matter intake (DMI), average daily gain (ADG), and feed conversion ratio (FCR) of small ruminants. Methods: A total of 12 studies (338 small ruminants) were included in this meta-analysis. The overall effect size was qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Other authors have observed that increased levels of EOs can decrease total digestibility. EOs have the potential to decrease the deamination of amino acids through their effect on ammonia-producing bacteria and protozoa [ 14 , 65 ]. The effect on NDF digestibility can be attributed to the control of the rumen bacterial populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have observed that increased levels of EOs can decrease total digestibility. EOs have the potential to decrease the deamination of amino acids through their effect on ammonia-producing bacteria and protozoa [ 14 , 65 ]. The effect on NDF digestibility can be attributed to the control of the rumen bacterial populations.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation with EOs could improve energy balance in small ruminants, where serum glucose and β-hydroxybutyrate (BHB) can be used as reliable indicators of ruminants’ energy status, while blood urea nitrogen (BUN) can indicate nitrogen metabolism [ 32 , 62 , 63 ]. While some studies have suggested that EO supplementation may improve metabolic health and energy metabolism [ 23 , 64 , 65 ], others have reported no significant effects on blood parameters [ 66 , 67 , 68 , 69 , 70 ]. Thus, it is necessary to determine the effect of EO supplementation on energy utilization, fat mobilization, and overall metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Although this practice provides economic benefits, the overuse of antibiotics evidently contributed to the existence of resistant microbes that threatens both human and livestock [4,5]. For that reason, many countries were then banned the use of antibiotics as growth promoting agents in the livestock sector [6,7]. This situation demanded the search for suitable alternatives to antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…However, the overuse of AGP led to the emergence of multi-resistant pathogenic microbes growth which threaten both animal and human health. [3][4][5] For this reason, the use of AGP is now prohibited in broiler production [3]. In Indonesia, the ban of AGP was started from 2018 [6].…”
Section: Introductionmentioning
confidence: 99%